2016
DOI: 10.1016/j.jnnfm.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability of shear-thinning fluids in deformable channels: Effect of inertial terms

Abstract: In the present work, the effect of inertial terms is numerically investigated on the hydroelastic stability of shearthinning fluids in pressure-driven flow between two parallel plates lined with a Mooney-Rivlin hyperelastic polymeric gel. Having obtained the basic flow for the fluid and the basic deformation for the solid, the vulnerability of the basic solutions are examined when subjected to infinitesimally-small, normal-mode perturbations. By dropping all nonlinear perturbation terms, an eigenvalue problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…(We have decided to go for the hardest scenario simply because in our recent publication dealing with compliant layers [20] we have already shown that the creeping-flow scenario may give rise to unrealistic behavior in the neutral stability curve.) We have reached to the following main conclusions:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(We have decided to go for the hardest scenario simply because in our recent publication dealing with compliant layers [20] we have already shown that the creeping-flow scenario may give rise to unrealistic behavior in the neutral stability curve.) We have reached to the following main conclusions:…”
Section: Discussionmentioning
confidence: 99%
“…25, we start with Eqs. [16][17][18][19][20]. At the basic state, poroelastic region consists of fluid and solid phases both under steady conditions.…”
Section: Appendix A: the Shear-thinning Aspect Of The Moore Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that the pressure difference causes the fluid to flow with no gravity influence and both the fluid and solid are of the same density and are incompressible. 51,52
Figure 1.Schematic of laminar flow in a two-dimensional channel with a compliant soft coating.
…”
Section: Geometry Description and Governing Equationsmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47][48][49][50] A variety of solid and fluid models have been used in previous studies when tackling this formidable fluid-solid interaction (FSI) problem. In a recent paper by Pourjafar et al, 51 the effect of inertia terms on the linear stability of shear-thinning fluids was investigated.…”
Section: Introductionmentioning
confidence: 99%